A novel trial of topotecan, ifosfamide, and carboplatin (TIC) in children with recurrent solid tumors. Issue 2 (8th November 2014) - Radhakrishnan, Kavita; Lee, Alice; Harrison, Lauren A.; Morris, Erin; Shen, Violet; Gates, Laura; Wells, Robert J.; Wolff, Johannes E.; Garvin, James H.; Cairo, Mitchell S.
<x xml:space="preserve">Abstract</x> Background Ifosfamide, carboplatin, and etoposide (ICE) in children with refractory or recurrent solid tumors and lymphomas has resulted in good overall response rates (ORR). Etoposide, a topoisomerase‐II inhibitor, however, has been associated with a significant increase in secondary leukemia. The rationale for substituting topotecan, a topoisomerase‐I inhibitor, for etoposide in this regimen, a topoisomerase‐II inhibitor, includes its limited toxicity profile and decreased leukemogenicity. Furthermore, topotecan in combination with both alkylators and platinating agents are additive and/or synergistic against a variety of solid tumors. Procedure Patients with relapsed/refractory solid tumors received ifosfamide (9 g/m2) and carboplatin (area under the curve: 3 mg/ml/min). Topotecan was also administered at 0.5 mg/m2/day × 3 days (N = 12) and in a small cohort (N = 3) at 0.75 mg/m2/day. Results Fifteen patients were entered onto study. Two patients developed seizures/encephalitis secondary to ifosfamide. One patient had dose‐limiting thrombocytopenia secondary to TIC that resolved with supportive care. Patients received a median of three cycles (1–3) of TIC. Of the 14 evaluable patients for response, 4/14 had a complete response (CR), 2/14 had a partial response (PR), and 1/14 patients had stable disease (SD). The ORR (CR + PR) was 43%. Conclusion TIC chemotherapy is feasible and tolerable in children and adolescents with refractory/recurrent solid tumors and lymphomas and results in a 43% excellent ORR in this poor‐risk group of patients. A larger cohort of patients, especially in Wilms tumor and central nervous system (CNS) tumors, should be studied in the future to attempt to confirm these preliminary findings. Pediatr Blood Cancer 2015;62:274–278. © 2014 Wiley Periodicals, Inc.